Morphogenesis and cell fate determination within the adaxial cell equivalence group of the zebrafish myotome. - Mai E Nguyen-Chi; Robert Bryson-Richardson; Carmen Sonntag; Thomas E Hall; Abigail Gibson; Tamar Sztal; Wendy Chua; Thomas F Schilling; Peter D Currie (PLoS Genetics, 2012)
One of the central questions of developmental biology is how cells of equivalent potential-an equivalence group-come to adopt specific cellular fates. In this study we have used a combination of live imaging, single cell lineage analyses, and perturbation of specific signaling pathways to dissect the specification of the adaxial cells of the zebrafish embryo. We show that the adaxial cells are myogenic precursors that form a cell fate equivalence group of approximately 20 cells that consequently give rise to two distinct sub-types of muscle fibers: the superficial slow muscle fibers (SSFs) and muscle pioneer cells (MPs), distinguished by specific gene expression and cell behaviors. Using a combination of live imaging, retrospective and indicative fate mapping, and genetic studies, we show that MP and SSF precursors segregate at the beginning of segmentation and that they arise from distinct regions along the anterior-posterior (AP) and dorsal-ventral (DV) axes of the adaxial cell compartment. FGF signaling restricts MP cell fate in the anterior-most adaxial cells in each somite, while BMP signaling restricts this fate to the middle of the DV axis. Thus our results reveal that the synergistic actions of HH, FGF, and BMP signaling independently create a three-dimensional (3D) signaling milieu that coordinates cell fate within the adaxial cell equivalence group.